Building Coalitions: Turf Issues - Gregory P. Siek; Carla E. Hague; Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY506, Part 14 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.